Glenoid Bone Loss in Posterior Shoulder Instability: Prevalence and Outcomes in Arthroscopic Treatment. Issue 5 (April 2018) - Hines, Adam; Cook, Jay B.; Shaha, James S.; Krul, Kevin; Shaha, Steve H.; Johnson, John; Bottoni, Craig R.; Rowles, Douglas J.; Tokish, John M.
Background: Glenoid bone loss is a well-accepted risk factor for failure after arthroscopic stabilization of anterior glenohumeral instability. Glenoid bone loss in posterior instability has been noted relative to its existence in posterior instability surgery. Its effect on outcomes after arthroscopic stabilization has not been specifically evaluated and reported. Purpose: The purpose was to evaluate the presence of posterior glenoid bone loss in a series of patients who had undergone arthroscopic isolated stabilization of the posterior labrum. Bone loss was then correlated to return-to-duty rates, complications, and validated patient-reported outcomes. Study Design: Case-control study; Level of evidence, 3. Methods: A retrospective review was conducted at a single military treatment facility over a 4-year period (2010-2013). Patients with primary posterior instability who underwent arthroscopic isolated posterior labral repair were included. Preoperative magnetic resonance imaging was used to calculate posterior glenoid bone loss using a standardized "perfect circle" technique. Demographics, return to duty, complications, and reoperations, as well as outcomes scores including the Single Assessment Numeric Evaluation and the Western Ontario Shoulder Instability Index (WOSI) scores, were obtained. Outcomes were analyzed across all patients based on percentage of posterior glenoid bone loss. Bone loss was then categorized as below or above the subcritical threshold of 13.5% to determine if bone loss effected outcomes similar to what has been shown in anterior instability. Results: There were 43 consecutive patients with primary, isolated posterior instability, and 32 (74.4%) completed WOSI scoring. Mean follow-up was 53.7 months (range, 25-82 months) The mean posterior glenoid bone loss was 7.3% (0%-21.5%). Ten of 32 patients (31%) had no appreciable bone loss. Bone loss exceeded 13.5% in 7 of 32 patients (22%), and 2 patients (6%) exceeded 20% bone loss. Return to full duty or activity was nearly 90% overall. However, those with >13.5%, subcritical glenoid bone loss, were statistically less likely to return to full duty (relative risk = 1.8), but outcomes scores, complications, and revision rates were otherwise not different in those with no or minimal bone loss versus those with more significant amounts. Conclusion: Posterior glenoid bone loss has not previously been evaluated independently relative to patients with shoulder instability repairs. Sixty-nine percent of our patients had measurable bone loss, and 22% had greater than 13.5%, or above subcritical bone loss. While these patients were statistically less likely to return to full duty, the reoperation rate, complications, and patient-reported outcomes between groups were not different.